KARAKTERISTIK SISWA SEBAGAI PIJAKAN DALAM PENELITIAN DAN METODE PEMBELAJARAN - C. Asri Budiningsih (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Learner Characteristics as a Basis for Teaching Method and Research on Instruction. The instructional technology focuses its analysis on the improvement of the instructional quality on the basis of instructional strategies or instructional method variables. Instructional methods variables are classified into three main categories: (1) organizational strategy, (2) delivery strategy, and (3) management strategy. The variables which greatly influence the utilization of instructtional methods are the instructional condition variables, classified into three categories: (1) objectives and characteristics of a field of study, (2) constraints and characteristics of a field of study, and (3) learner characteristics. The learner characteristics are students’ personal quality, such as their intelligence, prior knowledge, cognitive styles, learning styles, motivation, and socio-cultural factors, which greatly influence the process and result of the study. Learner characteristics will determine the selection of the management strategy, which is also related to the method to organize the learning process. The learner characteristics have to be accepted as a given condition and utilized as a basis for research on instruction. Keywords: instructional variables, learner characteristics